2021
DOI: 10.1038/s41598-021-86710-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activations in syntax-related regions for multilinguals while acquiring a new language

Abstract: The neuroscientific foundation of multilingualism, a unique cognitive capacity, necessitates further elucidation. We conducted an fMRI experiment to evaluate the acquisition of syntactic features in a new language (Kazakh) for multilinguals and bilinguals. Results showed that the multilinguals who were more proficient in their second/third languages needed fewer task trials to acquire Kazakh phonology. Regarding group differences, the reduction in response times during the initial exposure to Kazakh were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…To justify sample sizes in relation to what has been previously published, we performed a power analysis ( Mumford 2012 ) by using our previous work with a similar error-detection task (grammatical or ungrammatical) with speech sounds ( Umejima et al. 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To justify sample sizes in relation to what has been previously published, we performed a power analysis ( Mumford 2012 ) by using our previous work with a similar error-detection task (grammatical or ungrammatical) with speech sounds ( Umejima et al. 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…2021 ). We used the whole-brain data from a group of 15 participants (Bilingual group, G2 condition, “Sentence – Lexical list” contrast; see Umejima et al. 2021 ), according to a previous pilot study ( Durnez et al.…”
Section: Methodsmentioning
confidence: 99%
“…Among a wide range of people facing problems with sentence processing, L2 learners who have normal non-language ability (e.g., attention and executive function; compared to patients) enable us to make further investigations, by which the confounding effects brought by the non-language factors could be controlled to a relatively low extent. From recent studies, L2 learners were found to process sentences also with LPFC (esp., LIFG) highly involved, which suggested that L1 and L2 speakers share a common brain area in LPFC to accomplish sentence processing (e.g., Chen et al, 2019, 2021b; Golestani et al, 2006; Jeon & Frederici, 2013; Mueller et al, 2014; Nakagawa et al, 2022; Nachi & Sakai, 2009; Sakai et al, 2009; Tao et al, 2021; Umejima et al, 2021; Wartenburger et al, 2003). Specifically, Chen et al (2019, 2021b) proposed that native Korean speakers showed significant activation in posterior LIFG when reading artificial sentences generated by the Chinese-like grammar based on word category information.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum has a large capacity for plasticity and acquires language functions relatively early in development compared with the rest of the brain 8,20,21 . A theory that cerebellar language acquisition supports subsequent language acquisition in the neocortex 8,20,21 has been proposed based on recent observations that childhood damage to the right cerebellum causes more permanent and severe language deficits than adult damage [20][21][22][23] , and that the right cerebellum is activated during learning of new language tasks 15,24,25 . Understanding the circuit computations of language functions in the cerebellum is crucial to unravelling the mechanisms of human language processing.…”
Section: Introductionmentioning
confidence: 99%